2017
DOI: 10.1016/j.drugpo.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Down in the valley: Trajectories of injection initiation among young injectors in California’s Central Valley

Abstract: Background Injection drug use initiation represents a critical point of public health intervention, as injection increases risk forblood borne infections including Hepatitis C and HIV. In this paper, weexplore pathways to injection initiation among youth (<=30) in the ruralcontext of California’s Central Valley, where rates of injection drug useare among the highest in the nation. Methods We draw on semi-structured qualitative interviews with 20 younginjectors to examine drug use histories, including the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…12 Additionally, people who misuse prescription opioids are also at increased risk of subsequently injecting drugs. [32][33][34] Data from the current study show that individuals who report injecting drugs reported initiating injection an average of 4 years after starting non-injection opioid misuse. 19 may not yet be connected to testing.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…12 Additionally, people who misuse prescription opioids are also at increased risk of subsequently injecting drugs. [32][33][34] Data from the current study show that individuals who report injecting drugs reported initiating injection an average of 4 years after starting non-injection opioid misuse. 19 may not yet be connected to testing.…”
Section: Discussionmentioning
confidence: 73%
“…One practical consideration is that individuals may not disclose injection practices in healthcare settings as a means to avoid stigma, preventing clinicians from accurately differentiating these risk groups 12 . Additionally, people who misuse prescription opioids are also at increased risk of subsequently injecting drugs 32–34 . Data from the current study show that individuals who report injecting drugs reported initiating injection an average of 4 years after starting non‐injection opioid misuse 19 .…”
Section: Discussionmentioning
confidence: 89%
“…Research suggests that a range of influences shape the initiation of injection drug use, including age, gender, socio-economic position and structural shifts (Guise, Horyniak, Melo, McNeill, & Werb, 2017; Harocopos, Goldsamt, Kobrak, Jost, & Clatts, 2009; Syvertsen, Paquette, & Pollini, 2017). Injection drug use initiation has also been linked to a range of meanings and experiences for individuals, including cost-efficacy, pleasure and belonging (Guise et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other qualitative studies have focused on the route of administration transitions of youths with opioid use disorders, finding that this group largely attributed their transition to injection use to individual tolerance, cost, and shifting drug markets – findings that are consistent with those presented in this study [ 19 ]. Additionally, quantitative studies on this population found that lifetime prescription opioid dependence, early ago of prescription opioid initiation, use not attributed to self-medication of a health issue, and predominantly using prescription opioids non-orally were all significant predictors of youths transitioning to heroin [ 20 ]. By understanding the key role of route of administration and common myths shape key transition points for opioid users, practitioners will be allowed to develop effective harm reduction and prevention materials that target individuals already using prescription opioids, or in the early stages of heroin use.…”
Section: Discussionmentioning
confidence: 99%